Chinese doctors' views on workplace-based assessment: trainee and supervisor perspectives of the mini-CEX. Issue 1 (1st January 2021) - Liang, Yuying; Noble, Lorraine M.
ABSTRACT: Purpose : This study investigated whether the mini-clinical evaluation exercise (mini-CEX) has been successfully integrated into the Chinese context, following its introduction as part of the national general training programme. Materials and methods : Online questionnaires (N = 91) and interviews (N = 22) were conducted with Year 1 trainee doctors and clinical supervisors at a cancer hospital in China to explore users' experiences, attitudes and opinions of the mini-CEX. Results " Trainees were more likely than supervisors to report understanding the purpose of the mini-CEX and agree that it encouraged reflection and helped improve overall performance. Both trainees and supervisors felt that it provided a framework for learning, that it was useful in identifying underperformance, and that it informed learning progression. Groups were equally positive about the commitment of their counterpart in the process and valued the focus on detailed feedback. It was perceived as cultivating the learner–teacher relationship. Overall, both groups felt they 'bought in' to using the mini-CEX. However, concerns were raised about subjectivity of ratings and lack of benchmarking with expected standards of care. Conclusions : Chinese trainees and supervisors generally perceived the mini-CEX as an acceptable and valuable medical training tool, although both groups suggested enhancements to improve its efficacy.